2016
DOI: 10.1152/ajpendo.00218.2016
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxycholesterol impairs endothelial function and vasodilation by uncoupling and inhibiting endothelial nitric oxide synthase

Abstract: Endothelial dysfunction is a key early step in atherosclerosis. 25-Hydroxycholesterol (25-OHC) is found in atherosclerotic lesions. However, whether 25-OHC promotes atherosclerosis is unclear. Here, we hypothesized that 25-OHC, a proinflammatory lipid, can impair endothelial function, which may play an important role in atherosclerosis. Bovine aortic endothelial cells were incubated with 25-OHC. Endothelial cell proliferation, migration, and tube formation were measured. Nitric oxide (NO) production and supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Studies have demonstrated the capacity of incense smoke to induce oxidative stress and inflammation [36][37][38][39] , which may lead to significantly reduced vascular nitric oxide levels and increased levels of endothelin-1 and inflammatory mediators, such as granulocyte-macrophage-colony stimulating factor. The unregulated levels of these mediators would destruct the vascular vasodilation and constriction 40,41 , thereby promoting vascular dysfunction. It was suggested the water-soluble factions in particulate matter such as the transition metals with redox potential can also accelerate the process in membrane lipid peroxidation, which trigger endothelial cell mutations 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the capacity of incense smoke to induce oxidative stress and inflammation [36][37][38][39] , which may lead to significantly reduced vascular nitric oxide levels and increased levels of endothelin-1 and inflammatory mediators, such as granulocyte-macrophage-colony stimulating factor. The unregulated levels of these mediators would destruct the vascular vasodilation and constriction 40,41 , thereby promoting vascular dysfunction. It was suggested the water-soluble factions in particulate matter such as the transition metals with redox potential can also accelerate the process in membrane lipid peroxidation, which trigger endothelial cell mutations 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In the endothelium, HSP90 is part of a complex with endothelial nitric oxide synthase ((eNOS)/HSP90) [2224]. The dissociation of HSP90 causes uncoupling of eNOS, leading to the production of reactive oxygen species (ROS) and endothelial dysfunction [23]. This process might be initiated by pro-inflammatory lipids [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation of HSP90 causes uncoupling of eNOS, leading to the production of reactive oxygen species (ROS) and endothelial dysfunction [23]. This process might be initiated by pro-inflammatory lipids [23, 24]. Interestingly, uncoupling of NOS and the increased level of oxidative stress have also been reported in calcified stenotic aortic valves [25].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, COPs are known to trigger oxidative stress by increasing the generation of superoxide anion [ 51 , 52 ], and down-regulating the expression/activation of Nrf2 [ 53 ] Consistent with these results, many studies have reported increased COPs levels in the membranes of cells subjected to oxidative stress, as it has been detected in patients with diabetes mellitus [ 54 ], hiperlipidemia [ 28 ], chronic inflammatory processes and chronic renal failure [ 55 ]. In this regard, the oxysterol clearance mechanisms are probably less efficient in those situations [ 44 ], as it was observed in orchidectomized rats in wich the antioxidant activity was decreased [ 9 ].…”
Section: Discussionmentioning
confidence: 99%